2009
DOI: 10.1159/000264202
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Human Herpesvirus-7 DNA in Bronchoalveolar Lavage

Abstract: Objectives: Human herpesvirus-7 (HHV-7) is a highly seroprevalent virus that, following primary infection, establishes latency or persistence in some tissues, including lung. The aim of this study was to investigate the prevalence of HHV-7 in the lower respiratory tract of hospitalized adult patients. Methods: The prevalence of HHV-7 DNA was determined by quantitative real-time PCR in 212 bronchoalveolar lavage (BAL) samples obtained from 153 patients. The molecular epidemiology and clinical role of HHV-7 were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…However, other researchers have failed to find any differences (3,12,30). Thus, the clinical importance of HHVs infection in critically ill patients, is a subject of discussion and needs further well-designed observational studies (27,(30)(31)(32).…”
Section: Introductionmentioning
confidence: 99%
“…However, other researchers have failed to find any differences (3,12,30). Thus, the clinical importance of HHVs infection in critically ill patients, is a subject of discussion and needs further well-designed observational studies (27,(30)(31)(32).…”
Section: Introductionmentioning
confidence: 99%
“…HHV-7 detected in the lungs is recognized as a risk factor for interstitial pneumonia or idiopathic pulmonary fibrosis [ 51 ]. The positive rate of HHV-7 using PCR detection is 20.7%, and the viral load in immunosuppressed patients exceeds that in immunocompetent individuals [ 52 ]. In this research, the overall detection rate of HHV-7 is 20.18%, and 30% of immunosuppressed individuals harbor HHV-7, consistent with prior multicenter retrospective studies.…”
Section: Discussionmentioning
confidence: 99%
“…There are several reports on the increased detection of non-respiratory viruses involved in viral CAP in respiratory samples from immunocompetent patients, although at a lower frequency than in immunocompromised hosts. Besides, EBV has been the most commonly detected one, followed by HHV-7, HHV-6, and CMV at different rates among patients with various respiratory diseases (18)(19)(20). In two different reports on ARDS patients with unknown etiology, Bonizzoli reported a prevalence of 43% for EBV and 28% for HSV-1 and CMV (21), and in the second survey, Tachikawa et al found CMV (60%), EBV (45%), HSV-1 (31%), HHV-7 (2%), and HHV-6 (5%) (22).…”
Section: E G I O N E L L a P N E U M O P L H I L A V Z V H S V 2 H U M A N P A R E C H O V I R U S P A R C O V I R U S B 1 9 C Y T O M E mentioning
confidence: 99%